Francisella tularensis strain LVS resides in MHC II-positive autophagic vacuoles in macrophages - Hrstka, R; Krocová, Z; Cerný, J; Vojtesek, B; Macela, A; Stulík, J (Folia microbiologica, 2007)
The Francisella tularensis strain LVS phagosome disintegrates during the first few hours after bacterial entry and microbes are released to the cytosol. Within 12 h both rapid multiplication of microbes and a steep increase of apoptosis of infected macrophages occur. We searched for signals involved in the death of macrophages and detected molecules associated with the autophagy machinery cathepsin D, PTEN, p53 and LC3, whose levels or modification were influenced by ongoing in vitro tularemic infection. The sequestration of cytoplasmic F. tularensis LVS into autophagosomes was confirmed by co-localization of the LVS strain containing vacuoles with LC3 (an autophagosomal marker). We also demonstrated the presence of MHC II antigens in these autophagosomes, indicating that they might act as a source of endogenous tularemic antigens for presentation to CD4+ T lymphocytes.
Keywords: Microtubule-Associated Proteins; autofagie; Cell Line; kathepsin D; konfokální mikroskopie; fluorescenční mikroskopie; PTEN Phosphohydrolase; vakuoly; proteiny asociované s mikrotubuly; Vacuoles; nádorový supresorový protein p53; Cathepsin D; MHC antigeny II. třídy; Microscopy, Confocal; Animals; Autophagy; Microscopy, Fluorescence; zvířata; makrofágy; myši; buněčné linie; fosfohydroláza PTEN; Mice; Macrophages; Francisella tularensis; Tumor Suppressor Protein p53; Histocompatibility Antigens Class II